2016
DOI: 10.1186/s12968-017-0347-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Aortic Hemodynamics in Marfan Syndrome: New Insights from a 4D Flow Cardiovascular Magnetic Resonance Multi-Year Follow-Up Study

Abstract: BackgroundThe aim of this 4D flow cardiovascular magnetic resonance (CMR) follow-up study was to investigate longitudinal changes in aortic hemodynamics in adolescent patients with Marfan syndrome (MFS).Methods4D flow CMR for the assessment of in-vivo 3D blood flow with full coverage of the thoracic aorta was performed twice (baseline scan t1/follow-up scan t2) in 19 adolescent MFS patients (age at t1: 12.7 ± 3.6 years, t2: 16.2 ± 4.3 years) with a mean follow-up duration of 3.5 ± 1.2 years. Ten healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 38 publications
5
57
1
2
Order By: Relevance
“…Although axial and circumferential shear stress have been computed for the SSR calculation, limited differences were observed for both parameters between FSI and CFD simulations and between dilating and non-dilating patients in any directional shear stresses. Of note, the absence of relationship between WSS and progressive dilation found here has already been shown by other authors [52]. The much higher resolution of the FSI and CFD simulations with respect to 4D flow MRI implies that WSS (and derived parameters, such as SSR) cannot be directly compared between in silico and in vivo studies [51].…”
Section: Discussionsupporting
confidence: 56%
“…Although axial and circumferential shear stress have been computed for the SSR calculation, limited differences were observed for both parameters between FSI and CFD simulations and between dilating and non-dilating patients in any directional shear stresses. Of note, the absence of relationship between WSS and progressive dilation found here has already been shown by other authors [52]. The much higher resolution of the FSI and CFD simulations with respect to 4D flow MRI implies that WSS (and derived parameters, such as SSR) cannot be directly compared between in silico and in vivo studies [51].…”
Section: Discussionsupporting
confidence: 56%
“…4D flow MRI thus enables visualization and quantification of complex blood flow patterns in the thoracic aorta [12,13]. Recent 4D flow MRI studies showed promising results in Marfan patients supporting the notion that pathological blood flow profiles may contribute to aneurysm formation [14,15]. Further longitudinal studies are needed to assess the potential of 4D flow MRI as a potential imaging biomarker for progression of aortic dilatation.…”
Section: Introductionmentioning
confidence: 96%
“…Cardiac output increases progressively in labour, peaking at the time of delivery . The increase is likely to be reflected in greater aortic shear stress and although cases of dissection in labour are rare, the greater shear stress may cause endothelial damage, predisposing to dissection in the puerperium. However, in selected cases, e.g.…”
Section: Discussionmentioning
confidence: 99%